Goa Displayed in Goa: The 1860 Industrial Exhibition of Portuguese Colonial India - Vicente,Filipa Lowndes (2018)
In 1860, Goa hosted the Industrial Exhibition of Portuguese India with 230 exhibitors and over 4,000 articles on display, all described in a comprehensive printed catalogue. How can we explain that Goa, considered the most neglected Portuguese colony by the late 19th century, had an “industrial exhibition” five years before the first international exhibition to take place in Portugal, in 1865, and twenty years before the first exhibition held in a Portuguese colony, that of Cape Verde, in 1881? This article tries to understand the meaning of a local initiative that led to the display of Goa's entangled past, present, and future – a space which was ‘displayed' across time and described by many as a “country”, with its own identity, and separate from the “other” India.